Staying 'in sync' with others during COVID-19: Perceived positivity resonance mediates cross-sectional and longitudinal links between trait resilience and mental health. Issue 3 (4th May 2022) - Prinzing, Michael M.; Zhou, Jieni; West, Taylor N.; Le Nguyen, Khoa D.; Wells, Jenna L.; Fredrickson, Barbara L.
ABSTRACT: Shared positive emotions involving caring and synchrony – termed 'positivity resonance' – are associated with mental health. We hypothesized that, during the COVID-19 pandemic, individual differences in trait resilience would be linked with better overall mental health in part because those higher in trait resilience experience more positivity resonance. We surveyed respondents nationally in April and May of 2020 (total N = 1, 059), during pervasive stay-at-home orders. Participants completed self-reports of trait resilience and mental health and used the Day Reconstruction Method to describe their social and emotional experiences. Structural equation models showed perceived positivity resonance to mediate the links between trait resilience and mental health outcomes. Subsequent analyses showed these mediating effects to be independent of overall positive emotion and social interaction quantity (amongst nationwide adults). These results indicate that high-quality social connection played a uniquely important role in maintaining mental health during the COVID-19 pandemic.